ANALISA BUDAYA ORGANISASI DAN KEPUASAN KERJA PEGAWAI TERHADAP KINERJA PEGAWAI AGEN ASURANSI JIWA DI BUMIPUTERA KANTOR WILAYAH SYARIAH JAKARTA - Ruslan Ruslan (JMB : Jurnal Manajemen dan Bisnis, 2019)
The purpose of this study was to find out and explain scientifically the influence of organizational culture and job satisfaction on the performance of employees of the Bumiputera life insurance agent in the Jakarta Syariah Regional Office.This study uses a quantitative descriptive approach, namely a research approach carried out by processing and presenting data using the basis of a statistical numerical approach in the form of more concise information. This information can be represented by the mean, median, frequency, percentage and various diagrams. The data analysis method used in this study is the Multiple Linear Regression model. Based on the results of the study All independent variables positively influence the measured dependent variable. Based on the correlation matrix analysis between dimensions on organizational culture variables and employee agent employee performance, the strongest influence on the integrity dimension of the organizational culture variable on the independence dimension of the employee agent agent's performance variable. While the correlation matrix analysis between dimensions on the variable job satisfaction and employee agent insurance performance, the strongest influence on the dimensions of coworkers from the variable job satisfaction on the dimensions of the effectiveness of the variable employee performance insurance agent.